RE-EVALUATING THE CORE PRINCIPLES OF SECULARISM IN CONTEMPORARY INDIA - Naidu, S. T.; Unnithan, Arun V (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Secularism, a foundational pillar of India’s democracy, has played a pivotal role in maintaining the nation’s pluralistic fabric. However, recent socio-political developments necessitate a re-evaluation of its core principles to ensure fairness, inclusivity, and impartiality in governance. This study explores the historical context of secularism in India, its constitutional mandates, and the challenges posed by the politicization of religion and judicial ambiguities. Through a comparative analysis of Indian and Western secular frameworks, the paper emphasizes the need for policy reforms and judicial clarity. Ultimately, it advocates for a balanced approach where state neutrality and protection of minority rights co-exist, reinforcing the constitutional ethos of secularism in modern India.